The Ubiquitin Binding Protein TAX1BP1 Mediates Autophagasome Induction and the Metabolic Transition of Activated T Cells - Whang, Michael I. (Immunity, 2017)
During immune responses, naïve T cells transition from small quiescent cells to rapidly cycling cells. We have found that T cells lacking TAX1BP1 exhibit delays in growth of cell size and cell cycling. TAX1BP1-deficient T cells exited G(0) but stalled in S phase, due to both bioenergetic and biosynthetic defects. These defects were due to deficiencies in mTOR complex formation and activation. These mTOR defects in turn resulted from defective autophagy induction. TAX1BP1 binding of LC3 and GABARAP via its LC3-interacting region (LIR), but not its ubiquitin-binding domain, supported T cell proliferation. Supplementation of TAX1BP1-deficient T cells with metabolically active L-cysteine rescued mTOR activation and proliferation but not autophagy. These studies reveal that TAX1BP1 drives a specialized form of autophagy, providing critical amino acids that activate mTOR and enable the metabolic transition of activated T cells.